Ferroelectric capacitor with high dielectric constant and low loss
By introducing multi-component design and optimization processes into bismuth ferrate ceramic materials, ferroelectric capacitors with high dielectric constant and low loss were prepared, which solved the problems of low dielectric constant and large loss in existing bismuth ferrate ceramic materials. Higher dielectric performance and lower losses are achieved.
Patent Information
- Application Number
- CN202411292661.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-09-14
AI Technical Summary
The existing bismuth ferrate ceramic materials have low dielectric constant, large losses, and leakage current problems in actual devices, limiting their application.
Dielectric ceramic composition (BimAnBpCq)FeO3 and Bi(FemDnEpFq)O3 are used to prepare dielectric ceramics by solid phase reaction method, add adhesive to press into ceramic sheets, and sintered under the protection of inert gas to form ferroelectric capacitors, optimize the process Parameters to increase dielectric constant and reduce losses.
A ferroelectric capacitor with high dielectric constant and low loss is realized. Through the high entropy bismuth ferrate composition and multi-component design, the valence state is balanced, local heterogeneity is increased, residual polarization is reduced, and polarization performance is improved.
Smart Images

Figure CN119306488A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic capacitors, and in particular to a high dielectric constant and low loss ferroelectric capacitor based on entropy design. Background Art
[0002] As one of the most widely used passive electronic components, ceramic capacitors have many excellent characteristics compared with other types of capacitors, such as large specific capacity, good moisture and heat resistance, small dielectric loss, small series equivalent resistance, and a wide range of capacitance and temperature coefficient options. They are widely used in high-power electronics, electrical appliances and other fields, such as hybrid vehicles, aerospace, oil drilling, national defense, and energy storage, inversion, filtering, bypass, coupling and other fields in sustainable distributed energy power systems. In recent years, with the growth of consumer markets such as smart phones, tablet computers, and 3D TVs, the demand for ceramic capacitors has increased year by year.
[0003] Ferroelectric ceramic materials have a very high dielectric constant and are a very important class of dielectric materials. They are widely used in the electronics industry to prepare ceramic capacitors. Bismuth ferrite (BiFeO3), as a common ferroelectric ceramic material, has room temperature multiferroicity (ferroelectric Curie temperature is 1103K, antiferromagnetic Neel temperature is 643K), and its strong ferroelectricity makes it a very promising dielectric. However, pure bismuth ferrite is not easy to synthesize, and although bismuth ferrite has a large polarization as a strong ferroelectric, its saturation polarization characteristics make its dielectric constant not high, and its large reversal hysteresis makes its loss large. In addition, the leakage current caused by oxygen vacancies caused by the change of valence of iron ions and bismuth vacancies caused by the volatilization of bismuth atoms hinders the application of bismuth ferrite in practical devices.
[0004] In order to solve the above problems, the Chinese invention patent with authorization announcement number CN103936408B discloses a room temperature multiferroic barium and chromium co-doped bismuth ferrite ceramic and its preparation method, which belongs to the field of materials science. The chemical formula of the ceramic material is: Bi 1-x Ba x Fe 1-y Cr y O3, 0<x≤0.2, 0<y≤0.1. The raw materials BaCO3, Bi2O3, Cr2O3 and Fe2O3 are mixed and ball-milled according to the stoichiometric ratio, and calcined at 800-840℃ for 2 hours after drying; the powder is ball-milled again, and polyvinyl alcohol solution is added after drying. After sufficient grinding, it is pressed into sheets at a pressure of 472MPa using a tablet press; the binder is removed at 560℃ for 2h, and calcined at 890-920℃ for 2 hours to form porcelain. The multiferroic ceramics prepared by this invention have excellent ferroelectric and ferromagnetic properties at room temperature. However, its dielectric constant needs to be further improved and the loss needs to be further reduced. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a high dielectric constant, low loss ferroelectric capacitor with high dielectric constant and low dielectric loss.
[0006] To achieve the above object, the technical solution adopted by the present invention is: a high dielectric constant, low loss ferroelectric capacitor, the preparation raw materials of which include a dielectric ceramic composition, the dielectric ceramic composition includes (Bi m A n B p C q )FeO3、Bi(Fe m D n E p F q )O3, wherein A, B, and C are independently selected from one or more of Nd, La, Sm, Eu, Er, Dy, Al, and B; D, E, and F are independently selected from one or more of Ru, Sc, Al, Ga, Y, and In; m+n+p+q=1, 0≤m≤1, 0≤n≤1, 0≤p≤1, and 0≤q≤1.
[0007] Another object of the present invention is to provide a method for preparing the high dielectric constant, low loss ferroelectric capacitor, comprising the following steps:
[0008] Step S1, preparing dielectric ceramics by a solid phase reaction method: mixing oxide or carbonate powders containing Bi, A, B, C, D, E, F, and Fe respectively according to a stoichiometric ratio, ball milling after mixing, then drying and calcining the sample, cooling it naturally to room temperature, and then ball milling and sieving the calcined powder again to obtain dielectric ceramic powder;
[0009] Step S2, preparing a ceramic sheet: adding a binder to the dielectric ceramic powder prepared in step S1, mixing well and pressing into a disc, then sintering at a certain temperature for 1-3 hours, and naturally cooling to room temperature to obtain a ceramic sheet;
[0010] Step S3, preparation of ferroelectric capacitor: silver is applied to the upper and lower surfaces of the ceramic sheet prepared in step S2, respectively, and sintered at 780-820° C. for 13-20 min under the protection of inert gas to form a ferroelectric capacitor.
[0011] Preferably, the calcination temperature in step S1 is 800-850° C., and the calcination time is 3-5 h.
[0012] Preferably, an appropriate amount of deionized water and zirconium oxide beads are added during the ball milling process in step S1, and the ball milling time is 2-7 hours.
[0013] Preferably, the screening in step S1 is through a 800-1500 mesh sieve.
[0014] Preferably, the mass ratio of the dielectric ceramic powder to the adhesive in step S2 is 100:(0.1-0.3).
[0015] Preferably, the adhesive in step S2 is PVA 098-05 adhesive.
[0016] Preferably, the certain temperature in step S2 is 1000-1150°C.
[0017] Preferably, the inert gas in step S3 is any one of nitrogen, helium, neon and argon.
[0018] Preferably, the thickness of the silver coating in step S3 is 0.1-0.2 μm; and the thickness of the ceramic sheet is 0.6-0.8 μm.
[0019] Due to the application of the above technical solution, the present invention has the following beneficial effects: the present invention ensures valence balance and increases local heterogeneity through the reasonable selection of high entropy bismuth ferrite component composition and formula in the dielectric ceramic composition; multi-component high entropy design is carried out at the Bi position or the Fe position to achieve the purpose of improving local disorder, reducing residual polarization, improving polarization, and reducing material loss. Through the reasonable selection of preparation process parameters and the coordinated effect of the composition formula, the ferroelectric capacitor prepared has a high dielectric constant and low dielectric loss. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a cross-sectional scanning electron microscope image of Example 1 of the present invention. DETAILED DESCRIPTION
[0021] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.
[0022] Embodiment 1
[0023] Figure 1 As shown, a high dielectric constant, low loss ferroelectric capacitor, the preparation raw materials of which include a dielectric ceramic composition, the dielectric ceramic composition includes (Bi 0.5 La 0.2 Sm 0.2 Nd 0.1 )FeO3.
[0024] A method for preparing the high dielectric constant, low loss ferroelectric capacitor comprises the following steps:
[0025] Step S1, preparing dielectric ceramics by a solid phase reaction method: mixing bismuth oxide, lanthanum oxide, samarium oxide, neodymium oxide, and iron oxide powders according to a stoichiometric ratio, ball milling the mixture, and then drying and calcining the sample, cooling it naturally to room temperature, and then ball milling and sieving the calcined powder again to obtain dielectric ceramic powder;
[0026] Step S2, preparing a ceramic sheet: adding a binder to the dielectric ceramic powder prepared in step S1, mixing well and pressing into a disc, then sintering at a certain temperature for 1 hour, and naturally cooling to room temperature to obtain a ceramic sheet;
[0027] Step S3, preparation of ferroelectric capacitor: silver is applied to the upper and lower surfaces of the ceramic sheet prepared in step S2, respectively, and sintered at 780° C. for 13 minutes under the protection of inert gas to form a ferroelectric capacitor.
[0028] The calcination temperature in step S1 is 800° C., and the calcination time is 3 h. During the ball milling process in step S1 , an appropriate amount of deionized water and zirconium oxide beads are added, and the ball milling time is 2 h. The screening in step S1 is through an 800-mesh sieve.
[0029] The mass ratio of the dielectric ceramic powder and the adhesive in step S2 is 100:0.1; the adhesive in step S2 is PVA 098-05 adhesive; the certain temperature in step S2 is 1000° C.; the inert gas in step S3 is nitrogen; the thickness of the silver coating in step S3 is 0.1 μm; and the thickness of the ceramic sheet is 0.6 μm.
[0030] Embodiment 2
[0031] A high dielectric constant, low loss ferroelectric capacitor, the preparation raw materials of which include a dielectric ceramic composition, the dielectric ceramic composition includes Bi(Fe 0.25 Sc 0.25 Ru 0.1 Al 0.4 )O3.
[0032] A method for preparing the high dielectric constant, low loss ferroelectric capacitor comprises the following steps:
[0033] Step S1, preparing dielectric ceramics by solid phase reaction method: mixing bismuth oxide, scandium oxide, ruthenium oxide, aluminum oxide and iron oxide powders according to stoichiometric ratio, ball milling after mixing, then drying and calcining the sample, cooling naturally to room temperature, and then ball milling and sieving the calcined powder again to obtain dielectric ceramic powder;
[0034] Step S2, preparing a ceramic sheet: adding a binder to the dielectric ceramic powder prepared in step S1, mixing well and pressing into a disc, then sintering at a certain temperature for 1.5 hours, and naturally cooling to room temperature to obtain a ceramic sheet;
[0035] Step S3, preparation of ferroelectric capacitor: silver is applied to the upper and lower surfaces of the ceramic sheet prepared in step S2, respectively, and sintered at 790° C. for 15 minutes under the protection of inert gas to form a ferroelectric capacitor.
[0036] The calcination temperature in step S1 is 820° C., and the calcination time is 3.5 h. During the ball milling process in step S1, an appropriate amount of deionized water and zirconium oxide beads are added, and the ball milling time is 4 h. The screening in step S1 is through a 1000 mesh sieve.
[0037] The mass ratio of the dielectric ceramic powder and the adhesive in step S2 is 100:0.15; the adhesive in step S2 is PVA 098-05 adhesive; the certain temperature in step S2 is 1050° C.; the inert gas in step S3 is helium; the thickness of the silver coating in step S3 is 0.12 μm; and the thickness of the ceramic sheet is 0.65 μm.
[0038] Embodiment 3
[0039] A high dielectric constant, low loss ferroelectric capacitor, the preparation raw materials of which include a dielectric ceramic composition, the dielectric ceramic composition includes (Bi 0.5 Er 0.1 Dy 0.3 B 0.1 )FeO3.
[0040] A method for preparing the high dielectric constant, low loss ferroelectric capacitor comprises the following steps:
[0041] Step S1, preparing dielectric ceramics by a solid phase reaction method: mixing bismuth oxide, erbium oxide, dysprosium oxide, boron oxide, and iron oxide powders according to a stoichiometric ratio, ball milling the mixture, and then drying and calcining the sample, cooling it naturally to room temperature, and then ball milling and sieving the calcined powder again to obtain dielectric ceramic powder;
[0042] Step S2, preparing a ceramic sheet: adding a binder to the dielectric ceramic powder prepared in step S1, mixing well and pressing into a disc, then sintering at a certain temperature for 2 hours, and naturally cooling to room temperature to obtain a ceramic sheet;
[0043] Step S3, preparation of ferroelectric capacitor: silver is applied to the upper and lower surfaces of the ceramic sheet prepared in step S2, respectively, and sintered at 800° C. for 17 minutes under the protection of inert gas to form a ferroelectric capacitor.
[0044] The calcination temperature in step S1 is 830° C., and the calcination time is 4 hours; during the ball milling process in step S1, an appropriate amount of deionized water and zirconium oxide beads are added, and the ball milling time is 4 hours; the screening in step S1 is through a 1300 mesh sieve.
[0045] The mass ratio of the dielectric ceramic powder and the adhesive in step S2 is 100:0.2; the adhesive in step S2 is PVA 098-05 adhesive; the certain temperature in step S2 is 1100° C.; the inert gas in step S3 is neon; the thickness of the silver coating in step S3 is 0.15 μm; and the thickness of the ceramic sheet is 0.7 μm.
[0046] Embodiment 4
[0047] A high dielectric constant, low loss ferroelectric capacitor, the preparation raw materials of which include a dielectric ceramic composition, the dielectric ceramic composition includes Bi(Fe 0.4 Ga 0.25 Y 0.15 In 0.2 )O3.
[0048] A method for preparing the high dielectric constant, low loss ferroelectric capacitor comprises the following steps:
[0049] Step S1, preparing dielectric ceramics by a solid phase reaction method: mixing bismuth oxide, iron oxide, gallium oxide, yttrium oxide, and indium oxide powders according to a stoichiometric ratio, ball milling the mixture, then drying and calcining the sample, naturally cooling it to room temperature, and then ball milling and sieving the calcined powder again to obtain dielectric ceramic powder;
[0050] Step S2, preparing a ceramic sheet: adding a binder to the dielectric ceramic powder prepared in step S1, mixing well and pressing into a disc, then sintering at a certain temperature for 2.5 hours, and naturally cooling to room temperature to obtain a ceramic sheet;
[0051] Step S3, preparation of ferroelectric capacitor: silver is applied to the upper and lower surfaces of the ceramic sheet prepared in step S2, respectively, and sintered at 810° C. for 19 minutes under the protection of inert gas to form a ferroelectric capacitor.
[0052] The calcination temperature in step S1 is 840° C., and the calcination time is 4.5 hours; an appropriate amount of deionized water and zirconium oxide beads are added during the ball milling process in step S1, and the ball milling time is 6 hours; the screening in step S1 is through a 1400 mesh sieve; the mass ratio of the dielectric ceramic powder and the adhesive in step S2 is 100:0.25; the adhesive in step S2 is PVA 098-05 adhesive; the certain temperature in step S2 is 1130° C.; the inert gas in step S3 is argon; the thickness of the silver coating in step S3 is 0.18 μm; and the thickness of the ceramic sheet is 0.75 μm.
[0053] Embodiment 5
[0054] A high dielectric constant, low loss ferroelectric capacitor, the preparation raw materials of which include a dielectric ceramic composition, the dielectric ceramic composition includes (Bi 0.6 Er 0.1 Nd 0.2 Al 0.1 )FeO3.
[0055] A method for preparing the high dielectric constant, low loss ferroelectric capacitor comprises the following steps:
[0056] Step S1, preparing dielectric ceramics by a solid phase reaction method: mixing bismuth oxide, erbium oxide, neodymium oxide, aluminum oxide, and iron oxide powders according to a stoichiometric ratio, ball milling the mixture, and then drying and calcining the sample, cooling it naturally to room temperature, and then ball milling and sieving the calcined powder again to obtain dielectric ceramic powder;
[0057] Step S2, preparing a ceramic sheet: adding a binder to the dielectric ceramic powder prepared in step S1, mixing well and pressing into a disc, then sintering at a certain temperature for 3 hours, and naturally cooling to room temperature to obtain a ceramic sheet;
[0058] Step S3, preparation of ferroelectric capacitor: silver is applied to the upper and lower surfaces of the ceramic sheet prepared in step S2, respectively, and sintered at 820° C. for 20 minutes under the protection of inert gas to form a ferroelectric capacitor.
[0059] The calcination temperature in step S1 is 850° C., and the calcination time is 5 hours; an appropriate amount of deionized water and zirconium oxide beads are added during the ball milling process in step S1, and the ball milling time is 7 hours; the screening in step S1 is through a 1500 mesh sieve; the mass ratio of the dielectric ceramic powder and the adhesive in step S2 is 100:0.3; the adhesive in step S2 is PVA 098-05 adhesive; the certain temperature in step S2 is 1150° C.; the inert gas in step S3 is argon; the thickness of the silver coating in step S3 is 0.2 μm; and the thickness of the ceramic sheet is 0.8 μm.
[0060] Comparative Example 1
[0061] A high dielectric constant, low loss ferroelectric capacitor and a preparation method thereof, which is basically the same as Example 1, except that BiFeO3 is used instead of (Bi 0.5 La 0.2 Sm 0.2 Nd 0.1 )FeO3.
[0062] In order to further illustrate the beneficial technical effects of the high dielectric constant and low loss ferroelectric capacitors involved in each embodiment of the present invention, the high dielectric constant and low loss ferroelectric capacitors involved in Examples 1-5 and Comparative Examples 1-2 were subjected to relevant dielectric performance tests (dielectric constant, loss) at a frequency of 1kHz under an LCR bridge according to conventional methods in the industry, and hysteresis loop tests were performed under a Radiant ferroelectric instrument to extract the maximum polarization (100kV cm -1 ) and remanent polarization, the results are shown in Table 1.
[0063] Table 1
[0064]
[0065]
[0066] It can be seen from the data in Table 1 that the high dielectric constant, low loss ferroelectric capacitors according to the embodiments of the present invention have higher dielectric constants and lower dielectric losses than the comparative products.
[0067] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A high dielectric constant, low loss ferroelectric capacitor, characterized in that: The raw materials for its preparation include a dielectric ceramic composition, wherein the dielectric ceramic composition comprises (Bi m A n B p C q )FeO3、Bi(Fe m D n E p F q )O3, wherein A, B, and C are independently selected from one or more of Nd, La, Sm, Eu, Er, Dy, Al, and B; D, E, and F are independently selected from one or more of Ru, Sc, Al, Ga, Y, and In; m+n+p+q=1, 0≤m≤1, 0≤n≤1, 0≤p≤1, and 0≤q≤1.
2. A method for preparing a high dielectric constant, low loss ferroelectric capacitor according to claim 1, characterized in that: The steps include: Step S1, preparing dielectric ceramics by a solid phase reaction method: mixing oxide or carbonate powders containing Bi, A, B, C, D, E, F, and Fe respectively according to a stoichiometric ratio, ball milling after mixing, then drying and calcining the sample, cooling it naturally to room temperature, and then ball milling and sieving the calcined powder again to obtain dielectric ceramic powder; Step S2, preparing a ceramic sheet: adding a binder to the dielectric ceramic powder prepared in step S1, mixing well and pressing into a disc, then sintering at a certain temperature for 1-3 hours, and naturally cooling to room temperature to obtain a ceramic sheet; Step S3, preparation of ferroelectric capacitor: silver is applied to the upper and lower surfaces of the ceramic sheet prepared in step S2, respectively, and sintered at 780-820° C. for 13-20 min under the protection of inert gas to form a ferroelectric capacitor.
3. The method for preparing a high dielectric constant, low loss ferroelectric capacitor according to claim 2, characterized in that: The calcination temperature in step S1 is 800-850° C., and the calcination time is 3-5 hours.
4. The method for preparing a high dielectric constant, low loss ferroelectric capacitor according to claim 2, characterized in that: In the ball milling process in step S1, an appropriate amount of deionized water and zirconium oxide beads are added, and the ball milling time is 2-7 hours; the sieving in step S1 is sieving through a 800-1500 mesh sieve.
5. The method for preparing a high dielectric constant, low loss ferroelectric capacitor according to claim 2, characterized in that: The mass ratio of the dielectric ceramic powder to the adhesive in step S2 is 100:(0.1-0.3).
6. The method for preparing a high dielectric constant, low loss ferroelectric capacitor according to claim 2, characterized in that: The adhesive in step S2 is PVA 098-05 adhesive.
7. The method for preparing a high dielectric constant, low loss ferroelectric capacitor according to claim 2, characterized in that: The certain temperature in step S2 is 1000-1150°C.
8. The method for preparing a high dielectric constant, low loss ferroelectric capacitor according to claim 2, characterized in that: The inert gas in step S3 is any one of nitrogen, helium, neon and argon.
9. The method for preparing a high dielectric constant, low loss ferroelectric capacitor according to claim 2, characterized in that: The thickness of the silver coating in step S3 is 0.1-0.2 μm; the thickness of the ceramic sheet is 0.6-0.8 μm.
Citation Information
Patent Citations
A kind of room temperature multiferroic barium, chromium co-doped bismuth ferrite ceramics and preparation method thereof
CN103936408B
Dielectric ceramic composition and ceramic capacitor
WO2023080069A1